The role of the judiciary power in the realization of fundamental rights in the face of scarcity of public resources in the context of a pandemic - Verucy R. Barbosa, Jéssyca (2022)
The purpose of this article is to analyze the rationalization of decisions in ADPF 671 (universal right to health) and in ADI 6357 (non-application of the “golden rule” in respect of fundamental rights) of the Supreme Court dealing with constitutional “conflicts” involving the scarcity of public resources and the guarantees of fundamental rights, such as the right to health, life and the dignity of the human person in the face of the pandemic scenario (Covid-19). In this work, the premises of post-positivism were used to address the role of the Judiciary in guaranteeing a Democratic State of Law due to the judicialization of this stir in the current context of crisis. With this, the normatization of fundamental rights established in the Theory of Principles of the jusphilosopher Ronald Dworkin and his thesis of the correct answer will be emphasized. The methodology is based on a qualitative appraisal of books, jurisprudence and other scientific articles that bring resources on the Theory of Law aiming to assist the Judiciary in guaranteeing indispensable rights in the context of a pandemic, in addition to an appreciation of the correlated legislative set.